HEDYCHIUM SPICATUM BUCH-HAM. (KUCHRI), A TREASURE HOUSE OF ESSENTIAL OILS - KUMARI, ISHA; KAURAV, HEMLATA; CHAUDHARY, GITIKA (International Journal of Current Pharmaceutical Research, 2021)
Medicinal plants have a very significant role in the health care system. They are served as the primary source of modern drugs. One of such important medicinal plant is Hedychium spicatum Buch-ham. which belongs to the Zingiberaceae family (ginger family). The plant is commonly known as the spiked ginger lily in English and Kuchri in Hindi and Shati in Sanskrit. It is a commercially valuable plant due to its rhizomes. This rhizomatous plant holds a significant place in Ayurveda due to its extraordinary disease-curing properties. It is mentioned as Shwasahara mahakashaya dravya in Ayurveda. It is used in many folk cultures around the world as a remedy against many diseases like diarrhoea, liver-related problems, pain, vomiting, stomachache, inflammation, nausea, headache, fever etc. It is a therapeutically important plant due to the presence of numerous important essential oils as major phytochemical constituents like 1,8-Cineole, camphene, sabinene, β-pinene, myrcene, α-phellandrene, etc. The main therapeutic properties of the plant are anti-inflammatory, anti-microbial, hepatoprotective, tranquilizer, antipyretic, anti-diabetic, pediculicidal, anti-helminthic etc. The aim of the present review is to provide information related to phytochemistry, therapeutic properties, traditional uses of Hedychium spicatum in Ayurveda and folk medicinal system.